2019
DOI: 10.1016/j.jallcom.2019.03.356
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on electrocaloric effect in Li+ doped BaTiO3 ceramics

Abstract: Aging creates significant changes in the properties of the ferroelectric materials such as dielectric and piezoelectric properties. However, the influence of aging on the electrocaloric effect (ECE) has not yet been investigated. In this work, we investigate the effect of the aging on the ECE in acceptor (Li þ ) doped BaTiO 3 ceramics. We observe that aging induced defect polarization (P D ) reduces the saturation polarization of the doped samples until T c ¼ 115 C. Above that temperature P D loses its effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…28 Eventually, the c/a value decreases slightly when x = 0.06, which may result from the segregation at the grain boundary caused by small excessive Li ions. 18 The maximum value of c/a is 1.0073 obtained at x = 0.04. It could be concluded that the addition of Li is favorable to optimize the crystallographic structure of BT ceramics.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…28 Eventually, the c/a value decreases slightly when x = 0.06, which may result from the segregation at the grain boundary caused by small excessive Li ions. 18 The maximum value of c/a is 1.0073 obtained at x = 0.04. It could be concluded that the addition of Li is favorable to optimize the crystallographic structure of BT ceramics.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…15−17 For instance, Guvenc and Adem investigated the electrocaloric capacity in acceptor Li-doped BT ceramics. 18 Huang et al adopted Li + −Ho 3+ ionpair engineering to arouse the potential performance of electrostriction in BT ceramics and the large Q 33 of 0.06 m 4 C −2 obtained with low hysteresis in their work. 19 Lou et al analyzed the effect of the Li location in BT ceramics on the piezoelectric constant and dielectric property.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, in most studies, lead-free BaTiO 3 , zinc oxide (ZnO), BZT-BCT, KNN, zinc sulfide (ZnS) was preferred instead of PZT. [112,[129][130][131][132]135] In earlier studies, different piezoelectric nanocrystals have been used together to enhance the electrical output of piezoelectric NGs. Sabry and Hussein added ZnO nanorods and BaTiO 3 nanospheres fillers to the PVDF fiber matrix, and a 12 V electrical output was observed under a force of 1.5 N. [131] Mostly, the piezoelectric nanofillers added also induce the PVDF 𝛽-phase that contributes to the improvement of the electrical performance of the material.…”
Section: Electrospun Fiber-based Pengsmentioning
confidence: 99%
“…Barium titanate has an ABO 3 type perovskite structure where the Ba +2 ions occupy at the A‐sites and the Ti +4 at B‐sites. In order to improve the EC response of BT ceramics, many isovalent dopants/co‐dopants at A‐ or B‐site were recently investigated 21–23 . Herein, we report the synthesis of Ba 1− x Li x TiO 3 ( x = 0, 0.01, 0.02, 0.03, 0.04, and 0.05) ceramics by the conventional solid‐state reaction method and the effect of Li doping on dielectric, leakage current, ferroelectric, electrocaloric, and energy storage properties of BaTiO 3 ceramics were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%